Statistical Analysis Towards Improvement of Design Rainfall: Case Study of Peninsular Malaysia - Chin, Ren Jie; Lai, Sai Hin; Chang, Kian Boon; Jaafar, Wan Zurina Wan; Othman, Faridah (Springer Verlag, 2018)
The main focus of this study is to find a better approach for the improvement of rainfall intensity–duration–frequency (IDF) for Peninsular Malaysia by fitting the best statistical model to each data series. This is because IDF curve is generally used to determine the design rainfall in designing water resource structures. Data are collected from 60 selected rainfall stations in Peninsular Malaysia based on their completeness of data and coverage area. Two models are chosen and compared to derive the IDF relationship, which are fitting PDS to generalized Pareto (GPA) distribution (GPA/PDS) and fitting AMS to generalized extreme value (GEV) distribution (GEV/AMS). Based on the L-moment ratio diagram, it is found that the model based on fitting PDS to GPA distribution is more suitable in derivation of rainfall IDF relationship in Peninsular Malaysia. A software package containing Rain Event Mining Tool (RainEMT), Rain IDF and RainMap is developed to aid the study.